A COMPARATIVE ANALYSIS OF DIRECT STENTING VERSUS PRE-DILATION IN ST-ELEVATION MYOCARDIAL INFARCTION - SHAH, SB (Biological and Clinical Sciences Research Journal, 2024)
A major cardiovascular emergency, ST-Elevation Myocardial Infarction (STEMI), needs prompt and efficient intervention to restore blood flow to the ischemic myocardium. The decision between direct and pre-dilation stenting, two of the many techniques used in primary percutaneous coronary intervention (PCI), has been a topic of continuous discussion. This comparative study was performed at Ayub Teaching Hospital Abbottabad after obtaining approval from the ethical review committee for six months. A total of 75 patients were included in this study and were divided into two groups. The documented procedural outcomes were the use of Gp IIb/IIIa inhibitors, procedure time, total procedure cost, and procedural problems. The rates of the left ventricular ejection fraction (LVEF) at discharge, ventricular fibrillation, all-cause death, and a composite of major adverse cardiac events at 30-day follow-up were documented. The results have shown that Group A has 2.44% cases of no re-flow and no abrupt closure or dissection occurrences. Group B’s incidence rates were 5.88%, 2.94%, and 5.88%, respectively. The procedural time, Group A had an average of 33 ± 19 minutes, while Group B recorded a longer procedural time of 41 ± 17 minutes. Postoperatively, Group A showed a mean LVEF of 49.2 ± 8.8, no cases of cardiogenic shock or stroke, and a mortality rate of 2.44%. In contrast, Group B had a mean LVEF of 48.9 ± 9.2, encountered cardiogenic shock in 5.88% of cases, experienced a stroke in 2.94%, and recorded a mortality rate of 2.94%. Additionally, both groups exhibited ST-segment resolution, with rates of 80.49% in Group A and 67.64% in Group B. The analysis of patients undergoing coronary intervention for ST-elevation myocardial infarction (STEMI) suggests that direct stenting may yield more favorable results compared to pre-dilation.